Debranching enzymes decomposed corn arabinoxylan into xylooligosaccharides and achieved prebiotic regulation of gut microbiota in broiler chickens - Wu, Wei; Zhou, Huajin; Chen, Yanhong; Guo, Yuming; Yuan, Jianmin (Journal of animal science and biotechnology, 2023)
Corn arabinoxylan (AX) is a complicated and multibranched antinutritional factor, thereby proving the use of endo-xylanase (EX) to be marginally valid. This study focused on specific types of AX-degrading enzymes (ADEs) to exert the synergy of debranching enzymes and track the prebiotic potential of enzymatic hydrolysates. This study investigated the effects of ADEs on the growth performance, intestinal histomorphology, absorption functions, changes in polysaccharide components, fermentation, and gut microbiota of broiler chickens. Five hundred seventy-six five-day-old Arbor Acres male broiler chickens were randomly allocated into eight treatments with six replicates each. Corn basal diets supplemented with or without enzymes were fed for a 21-day period, specifically including EX, its compatible use with arabinofuranosidase (EXA) or ferulic acid esterase (EXF), and compound groups with the above three enzymes (XAF). Specific ADEs stimulated the jejunal villus height and goblet cell number and evidently decreased the crypt depth (P < 0.05), while the ratio of ileal villus height to crypt depth was significantly increased in EXF (P < 0.05). Maltase activities of ileal mucosa in XAF groups were extremely enhanced (P < 0.01), and EX boosted the activity of Na -K ATPase in the small intestine (P < 0.01). The insoluble AX concentrations comparatively lessened, thereby notably raising the sundry xylooligosaccharide (XOS) yield in the ileal chyme (P < 0.05), which was dominant in xylobiose and xylotriose. Improvements in the abundance and diversity of ileal microbial communities within the EXA, EXF, and XAF treatments were observed (P < 0.05). Positive correlations between microbiota and XOS were revealed, with xylobiose and xylotriose being critical for ten beneficial bacteria (P < 0.05). EXF increased the BWG and FCR of broiler chickens in this phase (P < 0.05), which was attributed to the thriving networks modified by Lactobacillus. The intracecal contents of acetic acid, butyric acid, and propionic acid were greatly enhanced in most ADE groups, such as EXF (P < 0.05). Debranching enzymes appreciably targeted corn AX to release prebiotic XOS in the posterior ileum and facilitated intracaecal fermentation. It was beneficial for improving gut development, digestion and absorption and modulating the microflora to promote the early performance of broiler chickens.